High-valence-element-doped single-crystal lithium-rich manganese oxide material as well as preparation method and application thereof

The synthesis of single-crystal lithium-rich manganese oxide materials doped with high-priced elements through co-precipitation and molten salt-assisted sintering method has solved the problem of poor circulation stability of existing materials and achieved efficient electrochemical performance improvement.

CN119824539APending Publication Date: 2025-04-15NANKAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510021555.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing lithium-rich manganese oxide positive electrode materials have problems such as irreversible oxygen precipitation and structural decay in the first circle, which affects its circulation stability.

Method used

Co-precipitation and molten salt-assisted sintering method are used to synthesize single-crystal lithium-rich manganese oxide materials with high-valent elements. Through the synergistic action of single-crystal structure and high-valent element doping, the structural stability and electrochemical performance of the material are improved.

Benefits of technology

The cyclic stability and electrochemical properties of the material are significantly improved, including the first-circle Coulomb efficiency and long-term cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824539A_ABST
    Figure CN119824539A_ABST
Patent Text Reader

Abstract

The invention relates to a high-valence-element-doped single-crystal lithium-rich manganese oxide material as well as a preparation method and application thereof, and belongs to the technical field of lithium ion battery positive electrode materials. The material comprises a single-crystal layered lithium-rich manganese oxide base material with good size dispersity and high-valence elements uniformly doped into the single-crystal layered lithium-rich manganese oxide base material, the size of the single crystal particles ranges from 200 nm to 500 nm; and the doping elements are high-valence elements such as Mo, Nb, Zr and the like. Benefited from the design of a single-crystal structure and the doping of high-valence elements, the material disclosed by the invention has excellent cycling stability; the release of oxygen, the side reaction of an interface and the irreversible phase change of a layered phase, a spinel phase and a rock salt phase in the electrochemical cycle process are all effectively inhibited. A lithium ion battery assembled by using the material as a positive electrode has high first-circle coulombic efficiency and excellent cycling stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery material preparation, and in particular, relates to the preparation and application of a high-valent element-doped single-crystal lithium-rich manganese oxide material. Background Art

[0002] Lithium-ion batteries have the advantages of high operating voltage, high energy density, long cycle life, low self-discharge, no memory effect and high cost performance, making them the main choice for secondary power sources in high-performance electric vehicles, smart grids, aerospace and other fields. Therefore, lithium-ion batteries and related materials have also become a hot topic for scientific researchers. Positive electrode materials are one of the key materials for lithium-ion batteries, limiting the energy density, power density, cycle life and safety of lithium-ion batteries. It is expected that by 2025, the energy density of new lithium-ion battery systems will be higher than 400Wh / kg. At present, LiCoO2, LiMn2O4, LiFePO4 and ternary materials are positive electrode materials with a high degree of commercialization, but the actual specific capacity has always been difficult to break through 220mAh / g. Therefore, the research and development of high energy density and low-cost positive electrode materials has become one of the main tasks in the field of lithium-ion batteries.

[0003] In recent years, lithium-rich manganese layered oxide cathode materials with high discharge capacity, high operating voltage and low cost have become the focus of attention. Its basic composition is xLi2MnO3·(1-x)LiMO2, where M is a mixture of transition metals (TMs) such as Ni, Mn, and Co. It is considered to be a new generation of cathode materials with great development prospects. However, lithium-rich manganese oxide cathode materials also have some problems, such as irreversible oxygen precipitation in the first cycle and structural decay during the cycle, which seriously affect the cycle stability of the material.

[0004] At present, the commonly used improvement strategies mainly include: 1. Physical coating of lithium-rich oxide positive electrode materials, such as coating with oxides such as Al2O3 and fluorides such as MgF2, to prevent direct contact between the electrode material and the electrolyte; 2. Structural design, gradient design of each element in the material or design of the morphology of the positive electrode material to inhibit oxygen release and improve the structural stability of the material; 3. Element doping occupies the lattice sites of Li / TM / O, thereby stabilizing the structure and inhibiting phase change; 4. Constructing oxygen vacancy defects, reducing the electron density of the surface O 2p state, and alleviating the irreversible release of surface oxygen.

[0005] Considering that the current single modification method still cannot fundamentally solve the problems faced by lithium-rich oxide cathode materials, it is necessary to adopt a combination of multiple modification methods. Using a simple and efficient method to comprehensively improve the electrochemical performance of lithium-rich manganese oxide cathode materials is extremely necessary for the commercial application of high-capacity lithium-rich manganese oxide materials. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a single crystal lithium-rich manganese oxide material doped with a high-valent element and a preparation method thereof, which are used to solve the problems in the prior art. Thanks to the design of the single crystal structure and the doping of high-valent elements, the material disclosed in the present invention has excellent cycle stability; the release of oxygen, interfacial side reactions, and irreversible phase transitions of layered phase-spinel phase-rock salt phase are effectively suppressed during the electrochemical cycle. The lithium-ion battery assembled using this material as the positive electrode has a high first-cycle coulomb efficiency and excellent cycle stability.

[0007] The specific implementation plan is as follows:

[0008] A high-valent element doped single-crystal lithium-rich manganese oxide material, characterized in that the material comprises a single-crystal layered lithium-rich manganese oxide substrate with good size dispersibility and a high-valent element uniformly doped into the single-crystal layered lithium-rich manganese oxide substrate;

[0009] The general structural formula of the single-crystal layered lithium-rich manganese oxide substrate is xLi2MnO3·(1-x)LiMO2, where M is selected from one or more of Ni, Mn, and Co, and 0≤x≤1;

[0010] The size of the single crystal layered lithium-rich manganese oxide substrate is distributed between 200nm and 500nm;

[0011] The high-valent element doped into the single-crystal layered lithium-rich manganese oxide substrate is Mo, Nb or Zr. ;

[0012] The present invention also discloses a method for preparing the high-valent element-doped single-crystalline lithium-rich manganese oxide material, which is specifically as follows:

[0013] Step (1): synthesizing a lithium-rich manganese oxide precursor material by a conventional coprecipitation method, and then preparing a lithium-rich manganese oxide positive electrode material by combining a high-temperature sintering method. Specifically, a manganese source, a nickel source or a cobalt source is dissolved in deionized water according to a stoichiometric ratio to form a 2 mol / L metal ion solution A, and then a mixed solution B of 2.1 mol / L Na2CO3 and 0.2 mol / L ammonia water is prepared. 200 ml of deionized water is added to the coprecipitation reactor as a base liquid, the water bath is kept at a constant temperature of 55°C, and argon gas is introduced for inert protection. The pumping speed of solution A and solution B is adjusted, and the pH during the reaction is monitored by a pH meter and maintained at about 7.7 to 7.8. After reacting for 12 hours, the mother liquor is discharged, allowed to stand for precipitation, and then washed and dried to obtain the precursor material;

[0014] Step (2): using a molten salt assisted sintering method to uniformly mix the precursor material obtained in step (1) with a molten salt medium, a lithium salt and a high-valent oxide dopant, and then placing the mixture in a box-type electric furnace, introducing oxygen as a sintering atmosphere, and sintering using a certain heating rate and a multi-step sintering procedure;

[0015] Step (3): washing, drying and re-sintering the sintered product obtained in step (2) to obtain a single-crystal lithium-rich manganese oxide material doped with a uniformly dispersed high-valent element.

[0016] The manganese source in step (1) is selected from at least one of MnSO4, Mn(NO3)2, Mn(CH3COO)2, and MnCl2, and the Ni source is selected from at least one of NiSO4, Ni(NO3)2, Ni(CH3COO)2, and NiCl2;

[0017] The mass ratio of the molten salt medium to the precursor used in step (2) is 1:1-3:1, and the molten salt medium is at least one of NaCl, KCl, and LiCl.

[0018] In step (2), the lithium salt is selected from at least one of LiOH·H2O, Li2CO3, LiNO3, Li(CH3COO), and LiF.

[0019] The high-valent oxide dopant used in step (2) is at least one of MoO3, Nb2O5, ZrO2, and WO3; the mass ratio of the dopant to the precursor is 1% to 5%.

[0020] In the multi-step sintering procedure of step (2), the temperature is first increased to 450-550°C at a rate of 2-5°C / min, sintered for 4-8h, then increased to 750-850°C at a rate of 2-5°C / min, kept at that temperature for 10-12h, and finally cooled naturally to room temperature.

[0021] The washing in step (3) is performed by alternating deionized water and ethanol for 3 to 5 times.

[0022] The drying process in step (3) is carried out in a vacuum drying oven at a temperature of 80-100° C. for 8-10 hours.

[0023] The secondary sintering procedure in step (3) is to increase the temperature to 400-500°C at a heating rate of 2-5°C / min, keep the temperature for 4-6 hours, and then cool naturally to obtain a single crystal lithium-rich manganese oxide material doped with a high-valent element with uniform size distribution.

[0024] The preparation method disclosed in the present invention combines coprecipitation and molten salt assisted sintering strategies to synthesize single-crystal lithium-rich manganese oxide materials doped with high-valent elements. Molten salt assisted sintering can provide a uniform and mild sintering environment, which is conducive to the fusion and growth of single crystal particles, and generates lithium-rich manganese oxide positive electrode materials with specific sizes and morphologies. Single crystal particles have the characteristics of no grain boundaries, no internal pores and low specific surface area, which can reduce side reactions with electrolytes, alleviate the accumulation of isotropic stresses between particles, and improve the structural stability of materials and the cycle performance of batteries. Since there is an ion concentration gradient between high-valent oxides and lithium-rich manganese oxide substrates, high-valent elements can be doped into the material by diffusion during the molten salt sintering process. High-valent elements combine with lattice oxygen to increase the strength of the oxygen element framework, reduce the irreversible precipitation of lattice oxygen under high voltage, and improve the first-cycle coulomb efficiency and long-term cycle stability. Combined with the design of single crystal structure and the strategy of high-valent element doping, the structural stability of lithium-rich manganese oxide positive electrode materials has been greatly improved.

[0025] It has been found through experiments that in the preparation method of the present invention, the performance of the lithium-rich manganese oxide material can be optimized by adjusting the amount of the high-valent oxide dopant.

[0026] Further preferably, in the above-mentioned method for preparing a single-crystalline lithium-rich manganese oxide material doped with a high-valent element, the separation in step 1 is carried out by vacuum filtration, and deionized water and ethanol are used for alternating washing for 3 to 5 times.

[0027] Further preferably, in the preparation method of the high-valent element-doped single-crystalline lithium-rich manganese oxide material as mentioned above, in the multi-step sintering procedure of step (2), the temperature is first increased to 500°C at a rate of 3°C / min, sintered for 5h, then increased to 800°C at a rate of 3°C / min, kept at this temperature for 12h, and finally naturally cooled to room temperature.

[0028] Further preferably, in the method for preparing the high-valent element-doped single-crystalline lithium-rich manganese oxide material, the drying process in step (3) is carried out in a vacuum drying oven at a temperature of 80-100° C. for 10 h.

[0029] By controlling the above parameters, the electrochemical properties of the finally prepared lithium-rich manganese oxide material can be regulated. With the continuous optimization of the above process parameters, the electrochemical properties of the finally prepared product are continuously optimized.

[0030] The present invention also discloses the application of the high-valent element doped single crystal lithium-rich manganese oxide positive electrode material in lithium-ion batteries. The lithium-ion battery is obtained by assembling the positive electrode sheets prepared with the high-valent element doped single crystal lithium-rich manganese oxide positive electrode material. The battery has high first-cycle coulombic efficiency and excellent cycle stability.

[0031] Compared with the existing lithium-rich manganese oxide materials, the present invention has the following advantages and progress:

[0032] The present invention combines co-precipitation and molten salt assisted sintering strategies to synthesize single crystal lithium-rich manganese oxide materials doped with high-valent elements. The prepared single crystal particle size is between 300nm and 500nm, and the high-valent elements are uniformly doped into the bulk phase of the lithium-rich manganese oxide material. The single crystal lithium-rich manganese oxide positive electrode material doped with high-valent elements has less oxygen release and less interfacial side reactions during long-term electrochemical cycles, which improves the structural stability of the lithium-rich manganese oxide matrix material during the cycle. In addition, the positive electrode sheet is prepared using the single crystal lithium-rich manganese oxide positive electrode material doped with high-valent elements and then assembled to obtain a lithium-ion battery, and the first cycle coulomb efficiency and cycle stability of the battery are greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 These are SEM images of different magnifications of a single-crystalline lithium-rich manganese oxide material doped with a high-valent element prepared in Example 1 of the present invention;

[0034] Figure 2 This is an XRD diagram of a single crystal lithium-rich manganese oxide material doped with a high-valent element prepared in Example 1 of the present invention;

[0035] Figure 3 HRTEM (a) and TEM-EDS (b) of a high-valent element-doped single-crystalline lithium-rich manganese oxide material prepared in Example 1 of the present invention;

[0036] Figure 4 This is an atomic-scale HADDF-STEM image of a single-crystalline lithium-rich manganese oxide material doped with a high-valent element prepared in Example 1 of the present invention;

[0037] Figure 5 This is an XPS spectrum of Mo 3d at different etching depths of a single crystal lithium-rich manganese oxide material doped with a high-valent element prepared in Example 1 of the present invention;

[0038] Figure 6 The first cycle charge and discharge curve (a) of the battery assembled with the single crystal lithium-rich manganese oxide material doped with high-valent elements in Example 1 at 0.1C (1C = 200mA / g) and the cycle performance curve (b) at 1C current density;

[0039] Figure 7 are SEM images of the lithium-rich manganese oxide material prepared in Comparative Example 1 at different magnifications;

[0040] Figure 8 is the XRD pattern of the lithium-rich manganese oxide material prepared in Comparative Example 1;

[0041] Fig. 9 HRTEM (a) and TEM-EDS (b) of the lithium-rich manganese oxide material prepared in Comparative Example 1;

[0042] Fig.10 is an atomic-scale HADDF-STEM image of the lithium-rich manganese oxide material prepared in Comparative Example 1;

[0043] Fig.11 This is the XPS energy spectrum of Mo 3d at different etching depths of the lithium-rich manganese oxide material prepared in Comparative Example 1;

[0044] Fig.12 The first cycle charge and discharge curve (a) of the battery assembled with the lithium-rich manganese oxide material prepared in Comparative Example 1 at 0.1C and the cycle performance curve (b) at 1C current density;

[0045] Fig.13 The cycle performance curve of the battery assembled with the lithium-rich manganese oxide materials prepared in Example 1 of the present invention and Comparative Example 1 at a 1C rate. DETAILED DESCRIPTION

[0046] The present invention is further described below in conjunction with specific embodiments and drawings. It should be noted that the specific implementation methods described herein are only for the purpose of illustrating and explaining the present invention and are not intended to limit the scope of protection of the present invention.

[0047] Embodiment 1:

[0048] Step (1): Use a conventional co-precipitation method to synthesize a lithium-rich manganese oxide precursor material, and then combine it with a high-temperature sintering method to prepare a lithium-rich manganese oxide positive electrode material. Specifically, the manganese source, nickel source, and cobalt source are dissolved in deionized water according to a stoichiometric ratio to form a 2 mol / L metal ion solution A. Then prepare a mixed solution B of 2.1 mol / L Na2CO3 and 0.2 mol / L ammonia water. Add 200 ml of deionized water as the base liquid to the co-precipitation reactor, keep the water bath temperature at 55°C, and introduce argon gas for inert protection. Adjust the pumping speed of solution A and solution B, and use a pH meter to monitor the pH during the reaction and keep it at about 7.7 to 7.8. After reacting for 12 hours, release the mother liquor, let it stand and precipitate, and then wash and dry to obtain the precursor material;

[0049] Step (2): using a molten salt assisted sintering method to uniformly mix the precursor material obtained in step (1) with a molten salt medium, a lithium salt and a high-valent oxide dopant. Then, the mixture is placed in a box-type electric furnace, oxygen is introduced as a sintering atmosphere, and sintering is performed using a certain heating rate and a multi-step sintering procedure;

[0050] Step (3): washing, drying and re-sintering the sintered product obtained in step (2) to obtain a single-crystal lithium-rich manganese oxide material doped with a uniformly dispersed high-valent element.

[0051] Figure 1 This is the SEM image of the high-valent element-doped single-crystalline lithium-rich manganese oxide positive electrode material prepared in this embodiment. It can be seen that the particle size of the synthesized material is between 200 and 500 nm, and the dispersion is good.

[0052] Figure 2 The XRD spectrum of the single crystal lithium-rich manganese oxide positive electrode material doped with a high-valent element prepared in this embodiment shows that the prepared lithium-rich manganese oxide positive electrode material has sharp diffraction peaks, good crystallinity, and exhibits characteristic peaks of a typical layered α-NaFeO2 layered structure. The weak diffraction peak between 2θ=20 and 25° belongs to the Li2MnO3 phase of the C2 / m space group.

[0053] Figure 3 HRTEM (a) and TEM-EDS (b) of the high-valent element doped single crystal lithium-rich manganese oxide positive electrode material prepared in this embodiment. Judging from the lattice fringe spacing in Figure (a), the synthesized material still maintains a typical layered structure inside. The lattice fringes with a crystal plane spacing of 0.478nm belong to the (003) crystal plane of the lithium-rich manganese oxide material. In addition, EDS energy spectrum analysis was performed on the high-valent element doped single crystal lithium-rich manganese oxide positive electrode material prepared in this embodiment. The results show that the distribution of elements such as Mn, Ni, Co, O and doped high-valent Mo in the material is uniform.

[0054] Figure 4 This is an atomic-scale HADDF-STEM image of a single-crystalline lithium-rich manganese oxide material doped with a high-valent element prepared in this example. The results show that the synthesized material still presents a typical layered structure with a crystal axis direction of [-100]. No signal belonging to the high-valent Mo element was observed in the Li layer, indicating that the doping site of the element is in the TM layer.

[0055] Figure 5 The following is the XPS spectrum of Mo 3d at different etching depths of the single crystal lithium-rich manganese oxide material doped with high-valent elements prepared in this example. The results in the figure show that the signal of the Mo element can be detected from the surface to the bulk of the material, indicating that the Mo element is successfully doped into the bulk of the material and is uniformly doped.

[0056] Performance Testing:

[0057] The high-valent element-doped single-crystal lithium-rich manganese oxide positive electrode material prepared in this embodiment is fully ground with SuperP conductive agent and PVDF binder in a mass ratio of 8:1:1, and then a certain volume of solvent NMP is added and stirred to mix evenly, and then coated on an aluminum foil current collector, and vacuum dried at 120°C for 12 hours to obtain a positive electrode sheet. A 2032 button cell is used, a metal lithium sheet is used as a reference electrode and a counter electrode, and a Celgard-2500 is used as a diaphragm, and the assembly is performed in a glove box. The electrolyte is LiPF6 (1.15 mol / L) / EC+DMC+EMC (volume ratio is 1:2:2). The test voltage window is 2.0~4.8V, and the electrochemical performance of the battery is tested by constant current charge and discharge.

[0058] Figure 6 The electrochemical performance of the battery assembled in this embodiment is shown in (a) the first cycle charge and discharge curve of the battery at a current density of 0.1C, and its first cycle coulomb efficiency can reach 91.7%, and the first cycle reversible capacity is 284.4mAh / g. (b) the cycle performance curve of the battery at a current density of 1C, after 100 cycles, the battery still has a discharge capacity of 277.6mAh / g, and the capacity retention rate is 97.6%.

[0059] Comparative Example 1

[0060] Step (1) is exactly the same as that in Example 1, and a precursor material for a lithium-rich manganese oxide positive electrode is prepared.

[0061] Step (2): The precursor material obtained in step (1) is mixed with a certain amount of Li2CO3 according to a stoichiometric ratio, pre-sintered at 500°C for 5 hours, and then sintered at 800°C for 12 hours to obtain a lithium-rich manganese oxide positive electrode material having a composition of Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2.

[0062] Figure 7 The SEM image of the lithium-rich manganese oxide positive electrode material prepared in this comparative example is different from the morphology observed in Example 1. The material prepared in this comparative example is a spherical secondary particle assembled by agglomerating smaller primary particles, which is a typical polycrystalline material. Its particle size distribution is about 10 μm.

[0063] Figure 8 The XRD spectrum of the lithium-rich manganese oxide positive electrode material prepared in this comparative example also shows a good layered structure with strong crystallinity.

[0064] Fig. 9HRTEM (a) and TEM-EDS (b) of the lithium-rich manganese oxide positive electrode material prepared in this comparative example. From the lattice fringe spacing in Figure (a), the material interior and surface layers maintain a typical layered phase. In addition, EDS energy spectrum analysis was performed on the lithium-rich manganese oxide positive electrode material prepared in this comparative example. The results show that the elements Mn, Ni, Co, O, etc. are evenly distributed in the material.

[0065] Fig.10 The HADDF-STEM image of the lithium-rich manganese oxide positive electrode material prepared in this comparative example at the atomic scale shows that the comparative material is a typical layered structure. The lattice fringes with a crystal plane spacing of 0.478nm belong to the (003) crystal plane of the lithium-rich manganese oxide material.

[0066] Fig.11 The XPS spectra of Mo 3d of the lithium-rich manganese oxide positive electrode material prepared in this comparative example at different etching depths show that no energy spectrum signal of the Mo element can be detected in this comparative example.

[0067] The test cell was assembled and its electrochemical performance was tested in the same manner as in Example 1.

[0068] Fig.12 The electrochemical performance of the battery assembled with the lithium-rich manganese oxide positive electrode material prepared in this comparative example, (a) shows the first cycle charge and discharge curve of the battery at a current density of 0.1C, and its first cycle coulomb efficiency can reach 76.9%, and the first cycle reversible capacity is 290.5mAh / g. (b) shows the cycle performance curve of the battery at a current density of 1C. After 100 cycles, the battery has a discharge capacity of 221.9mAh / g, and a capacity retention rate of 76.4%.

[0069] Fig.13 The cycle performance curve of the battery assembled with the lithium-rich manganese oxide material prepared in Example 1 and Comparative Example 1 at 1C rate. The test results show that the discharge specific capacity of the material in Example 1 after 100 cycles is 248.5 mAh / g, and the capacity retention rate reaches 96.3%. The capacity of the material in Comparative Example 1 after cycling is only 173.7 mAh / g, and the retention rate is 75.5%. Therefore, by utilizing the synergistic interaction between single crystal structure design and high-priced element doping, the cycle stability of the material in Example 1 has been greatly improved.

[0070] In summary, the present invention combines co-precipitation and molten salt assisted sintering methods to synthesize a high-valent element doped single crystal lithium-rich manganese oxide material, which is a method for effectively improving the comprehensive electrochemical performance of lithium-rich manganese oxide positive electrode materials. The molten salt ratio and the amount of dopant used will affect the performance of the material. By regulating the amount of the two, the excellent electrochemical performance of the material can be achieved. According to the above embodiment, the present invention can be well implemented. It should be further explained that the embodiments of the present invention do not cover all the selection combinations in the technical scheme. As long as the materials, amounts, process conditions, etc. involved in the technical scheme are within the technical scheme of the present invention, they are the same as the results of the embodiments of the present application. At the same time, the embodiments of the present application are not used to limit the scope of protection of the present invention. Any obvious adjustments and modifications to the technical scheme of the present invention that belong to the technical concept of the present invention should also fall within the scope of protection of the present invention.

Claims

1. A single crystal lithium-rich manganese oxide material doped with a high-valent element, characterized in that: The material comprises a single crystal layered lithium-rich manganese oxide substrate with good size dispersion and a high-valent element uniformly doped into the single crystal layered lithium-rich manganese oxide substrate; The general structural formula of the single-crystal layered lithium-rich manganese oxide substrate is xLi2MnO3·(1-x)LiMO2, where M is selected from one or more of Ni, Mn, and Co, and 0≤x≤1; The size of the single crystal layered lithium-rich manganese oxide substrate is distributed between 200nm and 500nm; The high-valent element doped into the single-crystal layered lithium-rich manganese oxide substrate is Mo, Nb or Zr.

2. The method for preparing the high-valent element-doped single-crystalline lithium-rich manganese oxide material according to claim 1, comprising: Step (1): synthesizing a lithium-rich manganese oxide precursor material by a conventional coprecipitation method, and then preparing a lithium-rich manganese oxide positive electrode material by combining a high-temperature sintering method. Specifically, a manganese source, a nickel source or a cobalt source is dissolved in deionized water according to a stoichiometric ratio to form a 2 mol / L metal ion solution A, and then a mixed solution B of 2.1 mol / L Na2CO3 and 0.2 mol / L ammonia water is prepared. 200 ml of deionized water is added to the coprecipitation reactor as a base liquid, the water bath is kept at a constant temperature of 55°C, and argon gas is introduced for inert protection. The pumping speed of solution A and solution B is adjusted, and the pH during the reaction is monitored by a pH meter and maintained at 7.7-7.

8. After reacting for 12 hours, the mother liquor is discharged, allowed to stand for precipitation, and then washed and dried to obtain the precursor material; Step (2): using a molten salt assisted sintering method to uniformly mix the precursor material obtained in step (1) with a molten salt medium, a lithium salt and a high-valent oxide dopant, and then placing the mixture in a box-type electric furnace, introducing oxygen as a sintering atmosphere, and sintering using a certain heating rate and a multi-step sintering procedure; Step (3): washing, drying and re-sintering the sintered product obtained in step (2) to obtain a single-crystal lithium-rich manganese oxide material doped with a uniformly dispersed high-valent element.

3. The method for preparing a high-valent element-doped single-crystalline lithium-rich manganese oxide material according to claim 2, characterized in that: The manganese source described in step (1) is selected from at least one of MnSO4, Mn(NO3)2, Mn(CH3COO)2, and MnCl2, and the Ni source is selected from at least one of NiSO4, Ni(NO3)2, Ni(CH3COO)2, and NiCl2.

4. The method for preparing a high-valent element-doped single-crystalline lithium-rich manganese oxide material according to claim 2, characterized in that: The mass ratio of the molten salt medium to the precursor used in step (2) is 1:1-3:1, and the molten salt medium is at least one of NaCl, KCl, and LiCl.

5. The method for preparing a high-valent element-doped single-crystalline lithium-rich manganese oxide material according to claim 2, characterized in that: In step (2), the lithium salt is selected from at least one of LiOH·H2O, Li2CO3, LiNO3, Li(CH3COO), and LiF.

6. The method for preparing a high-valent element-doped single-crystalline lithium-rich manganese oxide material according to claim 2, characterized in that: The high-valent oxide dopant used in step (2) is at least one of MoO3, Nb2O5, ZrO2, and WO3; the mass ratio of the dopant to the precursor is 1% to 5%.

7. The method for preparing a high-valent element-doped single-crystalline lithium-rich manganese oxide material according to claim 2, characterized in that: In the multi-step sintering procedure of step (2), the temperature is first increased to 450-550°C at a rate of 2-5°C / min, sintered for 4-8h, then increased to 750-850°C at a rate of 2-5°C / min, kept at that temperature for 10-12h, and finally cooled naturally to room temperature.

8. The method for preparing a high-valent element-doped single-crystalline lithium-rich manganese oxide material according to claim 2, characterized in that: The washing in step (3) is performed by washing with deionized water and ethanol alternately for 3 to 5 times; The drying process in step (3) is carried out in a vacuum drying oven at a temperature of 80-100° C. for 8-10 hours.

9. The method for preparing a high-valent element-doped single-crystalline lithium-rich manganese oxide material according to claim 2, characterized in that: The secondary sintering procedure in step (3) is to heat the temperature to 400-500° C. at a heating rate of 2-5° C. / min and keep the temperature for 4-6 hours, and then cool naturally to obtain a single crystal lithium-rich manganese oxide material doped with a high-valent element with uniform size distribution.

10. Application of the high-valent element doped single-crystal lithium-rich manganese oxide material according to claim 1 in lithium-ion batteries.